Structural and mechanical properties of ZnMgO nanoparticles - Tosun, M.; Ataoglu, S.; Arda, L.; Ozturk, O.; Asikuzun, E.; Akcan, D.; Cakiroglu, O. (Elsevier BV, 2014)
Abstract This study reports the effect of annealing temperature on the structure and mechanical properties of Zn 0.95 Mg 0.05 O bulk samples by using digital Vickers microhardness tester, X-ray diffraction analysis, scanning electron microscopy and electron dispersive X-ray measurements. The samples were prepared using Zn and Mg based alkoxed by the sol–gel technique and annealed at various temperatures (500, 600, 700 and 800 °C). Vickers microhardness, elastic modulus, yield strength and fracture toughness values of Zn 0.95 Mg 0.05 O bulk samples were separately calculated and compared with each other. The experimental results of hardness measurements were analyzed using Meyer's law, Proportional Specimen Resistance (PSR) and Elastic/Plastic Deformation (EPD) models and Hays–Kendall (HK) approach. Finally, it was seen that HK approach is the most successful model for the microhardness analysis of these materials.